Considerations on Integrating Prostate-Specific Membrane Antigen Positron Emission Tomography Imaging Into Clinical Prostate Cancer Trials by National Clinical Trials Network Cooperative Groups. Issue 13 (1st May 2022) - Schöder, Heiko; Hope, Thomas A.; Knopp, Michael; Kelly, William K.; Michalski, Jeff M.; Lerner, Seth P.; Tawab-Amiri, Abdul; Mann, Bhupinder S.; Lin, Daniel W.; Yu, Evan Y.; Chen, Ronald C.; Beach, Gillian C.; et al.
Abstract : PURPOSE: As prostate-specific membrane antigen (PSMA) positron emission tomography (PET) becomes increasingly available in the United States, the greater sensitivity of the technology in comparison to conventional imaging poses challenges for clinical trials. The NCI Clinical Imaging Steering Committee (CISC) PSMA PET Working Group was convened to coordinate the identification of these challenges in various clinical scenarios and to develop consensus recommendations on how best to integrate PSMA PET into ongoing and upcoming National Clinical Trials Network (NCTN) trials. METHODS: NCI CISC and NCI Genitourinary Steering Committee members and leadership nominated clinicians, biostatisticians, patient advocates, and other imaging experts for inclusion in the PSMA PET Working Group. From April to July 2021, the working group met independently and in conjunction with the CISC to frame challenges, including stage migration, response assessment, trial logistics, and statistical challenges, and to discuss proposed solutions. An anonymous, open-ended survey was distributed to members to collect feedback on challenges faced. Representatives from each NCTN group were invited to present an overview of affected trials. From these discussions, the consensus document was developed and circulated for the inclusion of multiple rounds of feedback from both the Working Group and CISC. RESULTS: The current consensus document outlines the key challenges for clinical prostate cancer trials resulting from the increasing availability of PSMA PET. We discuss implications for patient selection and definition of end points and provide guidance and potential solutions for different clinical scenarios, particularly with regard to best practices in defining eligibility criteria and outcome measures. RECOMMENDATIONS: This article provides guidance regarding clinical trial design and conduct, and the interpretation of trial results.